Simulation Analysis of the Leakage and Diffusion Risk of a Hydrogen Storage System in Hydrogen Aircraft - Xiangjun Dang; Mingwen Zhong; Wei Jia; Xiaojun Yang; Haoming Liu; Yongxuan Shao; Zhe Yang (Aerospace, 2025)
Hydrogen is an alternative energy source for the aviation industry due to its renewability and cleanliness, although this novel application needs to be reassessed for the potential leakage risk. For this reason, we take a small hydrogen-powered aircraft as the research object and investigate hydrogen diffusion behavior in the cabin after 35 MPa onboard hydrogen storage system leakage. Firstly, the effectiveness of the numerical simulation model is verified. Secondly, the numerical simulation model is utilized to simulate the changes in hydrogen mole fraction in the cabin under various scenario conditions (different leakage diameters, directions, and environment parameters). Finally, we investigate the impact of ventilation. Forced ventilation could significantly reduce the hydrogen mole fraction in the cabin in a short time. However, forced ventilation also promotes the diffusion of residual hydrogen in the cabin, resulting in a large proportion of the volume having a hydrogen mole fraction greater than 0.04, but it can significantly reduce the proportion of high hydrogen mole fraction (>0.1 or >0.2) regions.